Pentecostalism and politics of conversion in India - Sahoo, Sarbeswar
"Studies the politics of Pentecostal conversion and anti-Christian violence in India and answers the timely and relevant questions of why India is experiencing increasing incidents of anti-Christian violence since the 1990s"--